THE WORLD WOMEN'S VIEW FROM A WOMEN'S GROUP IN PORTO VELHO, BRAZIL, AT THE BEGINING OF THE 20TH CENTURY: PRELIMINARY RESEARCH NOTES - Rodrigues Mendonca, Joao Guilherme; Rodrigues, Marlene; Marcal Ribeiro, Paulo Rennes [UNESP] (Fundacao Univ Tocantins, 2020)
Porto Velho is a city with a little more than one hundred years, which was born from a reality shaped by American builders from the conglomerate surrounding the construction of the Madeira-Mamore Railway (1907-1912). In its beginning, it presented, in addition to the orderly zone that kept engineers, employees and families safe, another scenario, represented by a rurality of forest, Far West city, populated in a disorderly way that called itself Porto Velho dos Brasileiros. A large railway construction site that received workers from various parts of the world and Brazil, as well as a huge contingent of women who, having arrived there, left a legacy of life that guaranteed the ever-increasing expansion of the number of inhabitants. Using oral history, we aim to connect the `scraps' of the world lived and experienced by these fearless pioneers. We found that the women of Porto Velho were faced with a kaleidoscope of needs, and responded to them in the best possible way. True heroines: single, married, prostitutes, washerwomen, healers, and many others; they are the mothers of the children of that city.
Keywords: Women's history; Porto Velho's women; Madeira Mamore Railroad